Environmental Burden of Acute Respiratory Infection and Pneumonia due to Indoor Smoke - Dhimal, M; Baral, K; Shrestha, N; Dhakal, P; Maskey, M K (Journal of Nepal Health Research Council, 2010)
Background: ARI and pneumonia is one of the major public health problems in Nepal which always ranks highest  position among the top ten diseases. One  of the risk factor of ARI and pneumonia is indoor  smoke from kitchen where primary source of cooking is solid biomass fuel. This study was carried out in order to estimate the burden of  ARI and pneumonia  due to indoor  smoke. ARI and pneumonia  was chosen as it is one of the significant public health problem among under five children in Nepal and  responsible for high number of premature deaths.  Methods: A cross-sectional study was conducted in Dhading district. Multistage cluster sampling technique was used for data collection considering ward as a cluster. The environmental burden of ARI and pneumonia due to indoor smoke was calculated using the WHO Environmental Burden of Disease Series. Results: About 87 percent of households were using solid biomass fuel as a primarysource  of fuel. The under five children exposed to solid fuel use was 41313. The total 1284 Disability Adjusted Life Years were lost due to ARI and pneumonia and about 50 percent of it was attributed  by Indoor smoke  in household. Conclusions: The solid biomass fuel was primary source  of energy for cooking in Dhading  district which  is attributing about 50 percent of burden of ARI and pneumonia among under   five children. Key words: acute respiratory infection,environmental burden of disease, indoor smoke, pneumonia, solid fuel us